The C-SPAN Archives : An Interdisciplinary Resource for Discovery, Learning, and Engagement - Browning, Robert X., 1950- (Book collections on Project MUSE., 2014)
"The C-SPAN Archives record, index, and preserve all C-SPAN programming for historical, educational, and research uses. Every C-SPAN program aired since 1987, from all House and Senate sessions in the US Congress, to hearings, presidential speeches, conventions, and campaign events, totaling over 200,000 hours, is contained in the video library and is immediately and freely accessible through the database and electronic archival systems developed and maintained by staff. Whereas C-SPAN is best known as a resource for political processes and policy information, the Archives also offers rich educational research and teaching opportunities. This book provides guidance and inspiration to scholars who may be interested in using the Archives to illuminate concepts and processes in varied communication and political science subfields using a range of methodologies for discovery, learning, and engagement. The book links to illustrative clips from the Archives to help readers appreciate the usability and richness of the source material and the pedagogical possibilities it offers"--